2023
DOI: 10.3847/2041-8213/acb599
|View full text |Cite
|
Sign up to set email alerts
|

A Second Earth-sized Planet in the Habitable Zone of the M Dwarf, TOI-700

Abstract: We report the discovery of TOI-700 e, a 0.95 R ⊕ planet residing in the Optimistic Habitable Zone (HZ) of its host star. This discovery was enabled by multiple years of monitoring from NASA’s Transiting Exoplanet Survey Satellite (TESS) mission. The host star, TOI-700 (TIC 150428135), is a nearby (31.1 pc), inactive, M2.5 dwarf (V mag = 13.15). TOI-700 is already known to host three planets, including the small, HZ planet, TOI-700 d. The new planet has an orbital period of 2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 85 publications
0
7
0
Order By: Relevance
“…The period of 272 days makes this planet the second longest-period confirmed planet identified in the TESS data to date (with the longest being TOI 4600c, Mireles et al 2023), and only one of five confirmed TESS planets with orbital periods longer than 100 days (Dalba et al 2022;Heitzmann et al 2023). Furthermore, the long orbital period and incident flux of ∼1.6 F ⊕ places it in the habitable zone of its host star, making it only the fourth habitable zone planet identified in the TESS data to date, following TOI 700 d (Gilbert et al 2020;Rodriguez et al 2020), TOI 700 e (Gilbert et al 2023), and TOI 715 b (Dransfield et al 2024).…”
Section: Introductionmentioning
confidence: 86%
“…The period of 272 days makes this planet the second longest-period confirmed planet identified in the TESS data to date (with the longest being TOI 4600c, Mireles et al 2023), and only one of five confirmed TESS planets with orbital periods longer than 100 days (Dalba et al 2022;Heitzmann et al 2023). Furthermore, the long orbital period and incident flux of ∼1.6 F ⊕ places it in the habitable zone of its host star, making it only the fourth habitable zone planet identified in the TESS data to date, following TOI 700 d (Gilbert et al 2020;Rodriguez et al 2020), TOI 700 e (Gilbert et al 2023), and TOI 715 b (Dransfield et al 2024).…”
Section: Introductionmentioning
confidence: 86%
“…TOI-700 is an M2.5 dwarf star that hosts three planets discovered by TESS, with four planets (Kirkpatrick et al 1991;Gilbert et al 2020Gilbert et al , 2023Rodriguez et al 2020). Two of these planets, TOI-700 d and TOI-700 e, are Earth-sized planets in the habitable zone of the star (Gilbert et al 2020(Gilbert et al , 2023Rodriguez et al 2020). The SMs (S s , S c ) for this system are (103.0, 16.0).…”
Section: Appendix a A Simplified Expression Of Mass Concentration For...mentioning
confidence: 99%
“…In Table 5, we compare the TSM values between the TOI-2095 planets and other VZ planets that have equilibrium temperatures less than 400 K (TRAPPIST-1 d, TRAPPIST-1 c, TOI-237 b, and TOI-700 e; Gillon et al (2016), Waalkes et al (2021), Gilbert et al (2023)). Although six confirmed VZ planets with R p < 1.5R ⊕ have higher TSM values, the TOI-2095 planets offer observational advantages.…”
Section: Prospects For Atmospheric Characterizationmentioning
confidence: 99%